(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the self-image, Nutritional Status and Eating Behavior of users of the Psychosocial Care Center Methodology: This is a quantitative, descriptive and cross-sectional study carried out with adult users of CAPS, in the metropolitan region of Belém/PA. Questionnaires with socioeconomic and anthropometric variables, Kakeshita Silhouette Scale (1983), Image Avoidance Questionnaire (BIAQ) and Dutch Food Behavior Questionnaire (QHCA) were used. For statistical analysis, the BioEstat software, version 5.3 was used. The Shapiro-Wilk test, Spearman’s Correlation test, Student’s t test and Chi-square test were applied. A significance of 5% was adopted for the study. Results: According to age group, there are 35+11, 42% women and 58% men. Most were white (44%), followed by browns (34%) and blacks (22%). In total, 20 ICDs were identified, with F10, F31, F32, F29 AND F41.2 being the most prevalent. 4% were underweight, 44% eutrophic, 28% overweight and 24% obese. On the silhouette scale, 16 individuals had negative, 26 positive and 8 minimal distortion. Males had higher BIAQ and QHCA scores, 32.5 and 85.2, as opposed to 27.6 and 79.9 for females. A significant and directly proportional relationship was found between BMI and QHCA (p<0.001) Conclusion: Although there is multidisciplinary care at CAPS, eating disorders and their impacts on mental health are little considered, so strategies to identify nutritional risk are necessary regarding self-image and its impact on Eating Behavior.